1985
DOI: 10.1038/jcbfm.1985.13
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric Imaging of Blood Flow and Metabolism after Middle Cerebral Artery Occlusion in Cats

Abstract: In anesthetized adult cats, acute stroke was produced by transorbital occlusion of the left middle cerebral artery. A battery of imaging techniques was used for simultaneous evaluation of regional blood flow, glucose utilization, protein synthesis, pH, and the regional tissue content of glucose, ATP, and potassium. The electrophysiological impact of stroke was monitored by EEG frequency analysis and recording of somatosensory evoked potentials. Two hours after vascular occlusion, a close correlation existed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0
1

Year Published

1985
1985
2003
2003

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 89 publications
(33 citation statements)
references
References 45 publications
(14 reference statements)
4
28
0
1
Order By: Relevance
“…This suggests that the low-energy yield of nonoxidative metabolism prolongs the time required to restore membrane polarization and thus enhances the ionic disturbances that occur during the passage of DC shifts. The previously reported heterogeneous dissociation between flow, metabo lism, and ion homeostasis in the periphery of the experimental infarcts of cats is also in line with this interpretation (Hossmann et al, 1985).…”
Section: Discussionsupporting
confidence: 76%
“…This suggests that the low-energy yield of nonoxidative metabolism prolongs the time required to restore membrane polarization and thus enhances the ionic disturbances that occur during the passage of DC shifts. The previously reported heterogeneous dissociation between flow, metabo lism, and ion homeostasis in the periphery of the experimental infarcts of cats is also in line with this interpretation (Hossmann et al, 1985).…”
Section: Discussionsupporting
confidence: 76%
“…This early ischemic zone was frequently bordered by a rim of apparently enhanced glucose utilization, sug gesting the occurrence of anaerobic glycolysis. Re cently, Hossmann et al (1985) reported a hetero geneous pattern of glucose utilization within the re gion of the developing infarct 2 h following MCA occlusion. In one study, a mild suppression of cor tical glucose utilization was documented within the contralateral nonischemic hemisphere 90 min fol lowing MCA occlusion (Ginsberg et aI., 1977), while another study has reported a 20% decrease in glucose utilization throughout the brain 2 h after MCA occlusion (Hossmann et aI., 1985).…”
mentioning
confidence: 99%
“…The measurement of brain functional biochem istry has been given new impetus by the develop ment of a wide range of autoradiographic methods for assessing the physiological variables under normal conditions (Sokoloff et aI., 1977;Sakurada et aI., 1978;Mies et aI., 1981;Forlow et aI., 1983;Ginsberg et aI., 1986;Lear et aI., 1982;Mies et aI., 1986) and pathological conditions (Sako et aI., 1984b, and1985;Kato et aI., 1985;Hossmann et aI., 1985).…”
mentioning
confidence: 99%